America's road to empire : foreign policy from independence to World War One - Gleijeses, Piero (London, England : Zed Books, 2021)
"America's Road to Empire surveys and analyses United States foreign relations from the country's independence in 1776 until its entry into World War One in 1917, using primary source materials and case studies. The book covers key themes including: - the role that notions of "white superiority" played in US foreign policy - the search for absolute security that repeatedly led the United States to trample on the liberties of other countries; - and the idea of American 'exceptionalism' - the clash between the idealism of US rhetoric and its actions - which has led to a persistent failure to understand how "European" U.S. policy actually was. Whilst providing analytical overview, Piero Gleijeses also uses case studies which examine overlooked aspects of U.S. foreign policy, particularly concerning marginalized populations. He draws on archival U.S. and European primary sources and incorporates the latest research from the US, British, French and Spanish archives, as well as newspapers from the United States, Britain, France, Germany, Spain, and Mexico. A highly original account of the United States' rise to power drawing on multilingual scholarship, this is an important book for all students and scholars of United States foreign relations up to the First World War"--
Independence -- The Federalist era -- The Louisiana Purchase -- Jefferson's second term -- The war of 1812 -- The limits of sympathy : the independence of Spanish America -- Indian removal : a "sickening mass of putrefaction." -- Manifest destiny -- The 1850s and the Civil War -- After Appomattox -- Cuba and the Philippines -- Conquering the backyard -- The Far East -- The white city on the hill.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Imperialism; Modern history to 20th century: c 1700 to c 1900; United States -- Foreign relations -- 1783-1865.; United States -- Foreign relations -- 1865-1921.; United States -- Territorial expansion; United States -- Colonial question; Electronic books